Lung transplantation delays gastric motility in patients without prior gastrointestinal surgery—A single‐center experience of 412 consecutive patients. Issue 10 (21st September 2017) - Hirji, Sameer A.; Gulack, Brian C.; Englum, Brian R.; Speicher, Paul J.; Ganapathi, Asvin M.; Osho, Asishana A.; Shimpi, Rahul A.; Perez, Alexander; Hartwig, Matthew G.
Abstract: Purpose: To examine the impact of lung transplantation on gastric motility. Methods: Adult recipients at a large, single center, who were retrospectively evaluated with solid gastric emptying (SGE) study post‐lung transplantation, but had no history of gastrointestinal intervention (ie, pyloroplasty or fundoplication), were selected between June 2005 and August 2013. Multivariable logistic regression was performed to determine risk factors associated with delayed gastric emptying (DGE) after transplantation. Results: Delayed gastric emptying (DGE) was noted in 236 patients (57%) after transplantation. On multivariable logistic regression, an underlining diagnosis of cystic fibrosis (CF)/bronchiectasis (adjusted odds ratio [AOR] 3.26, P  < .01) was a significant risk factor in predicting DGE after lung transplantation. There was no survival difference between patients with postoperative DGE vs those without (log‐rank test P  = .53). Conclusions: Delayed gastric emptying is very common following lung transplantation, occurring in over half of all lung transplant recipients with increased prevalence in patients with CF. The association with cystic fibrosis could be secondary to extra‐pulmonary manifestations of the underlying disease or indicative of increased intraoperative vagal nerve injury. We speculate that DGE may play a substantial role in the increased reflux‐induced allograft injury seen after lung transplantation. Further prospective studies are needed to validate this hypothesis.